Auditoría energética para redes de alumbrado público exterior en el AEIRNNR de la Universidad Nacional de Loja. - Pinos López, María Soledad (2014)
Street lighting is an important fragment of the electricity sector, as it is determined as a necessity in the daily performance in modern human life, influencing its development and contributing to its security. This study aims to analyze a technological alternative , that over the years has been improved to the point of being presented around the world as an optimization option lighting systems , the technology called " magnetic induction " is not new but its great advances in recent years , justify its use . The different chapters of this study give a sequence analysis of induction lamps compared to other types of lamps used in streetlights: those that are currently being used in the city of Loja and using LED technology have also presented considerable technological advance. This sequence determines its inception , the definition of the concepts necessary for understanding throughout this study , then specify the necessary qualities and standards used for street lighting as best meets their goals later analysis is performed selected lamps and an entire chapter devoted to magnetic induction lamps , then the comparison between different parameter lamps , as well as measurements and simulations of the current state of a strip of the National University of Loja (UNL) , accompanied by the simulation of the behavior that would have the same range with induction lamps . In the end it makes a financial analysis comparing a brand new installation of lamps high pressure sodium against an installation of magnetic induction lamps and an additional alternative magnetic induction lamps using intelligent lighting controls , all in the Energy’s Area , Industry and non-Renewable Natural Resources (AEIRNNR). The study and its findings, emphasize that the decision to implement magnetic induction lamps and particularly those that use smart controls also depends on a financial analysis of the interest that you have the entities regulating lighting energy efficiency and vision lighting behavior in visual comfort and more important with regard to the influence this performance brand within, integrity and security of citizens